EKSISTENSIALISME DALAM TUNGGU AKU DI SUNGAI DUKU - Dessy Wahyuni (Balai Bahasa Provinsi Riau, 2012)
The short stories collection Tunggu Aku di Sungai Duku by Hary B. Koriun presents existentialism, a form of waiting. His eleven stories are about the loyalty of waiting something expected. Despite all these waitings have caused injuries, they remained faithful to do them. With all the freedom, the characters in the short stories have represented an existentialism. Through socio-hermeneutic approach to literature, this study aims to determine the forms of waiting that represents an existentialism in the sh ort stories collection. By using the descriptive analysis, it can be c oncluded that all forms of waiting they are doing is a form of self-existence.